PROTOTYPE ALAT PEMILAH HASIL PRODUKSI OLI OTOMATIS BERDASARKAN KODE WARNA MENGGUNAKAN SENSOR TCS 230 - Diah Aryani; Endang Sunandar; Fajar Ramadhan (Journal Cerita: Creative Education of Research in Information Technology and Artificial Informatics, 2019)
The role of technology that is growing very rapidly influences various domains including the industrial world of the company in meeting the increasing demands of the industry. So that it requires speed, accuracy, and accuracy in the sorting process, with the advancement of informationtechnology today. At PT Agheo Langgeng Chemindo for the process of sorting oil production is still manual, namely by moving the cardboard box produced to storage using human power and lifting it one by one which is quite draining. So that manual sorting is less efficient, technologicaladvancements are needed to save time and energy, and provide more benefits for the industry. Then the research is done by using hardware and software design methods that aim to make the Oil Production Result Sorting Tool Based on Color Code, this tool uses NodeMCU ESP8226 as amicrocontroller, TCS 230 color sensor as a color code reader and uses a servo motor as a separator, as a result of this study expected to be able to help users or owners of companies to simplify the sorting process that is more efficient and can provide benefits according to industry goals.